ANALISIS PENGARUH RASIO LANCAR, RASIO PERPUTARAN TOTAL AKTIVA, DEBT TO EQUITY RATIO, RETURN ON EQUITY, DAN EARNING PER SHARE TERHADAP RETURN SAHAM PERUSAHAAN SEKTOR INFRASTRUKTUR, UTILITAS, DAN TRANSPORTASI YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2 - KEN ADITYA; ISNURHADI . (JURNAL MANAJEMEN DAN BISNIS SRIWIJAYA, 2013)
The objective of this research is to examine the effect of current ratio, total asset turnover, debt to equity ratio, return on equity, and earning per share to stock return of infrastructure, utility, and transportation on Indonesia Stock Exchange period of 2007-2011. Independent variables used on this research are current ratio, total asset turn over, debt to equity ratio, return on equity, and earnings per share whereas stock return as dependent variable. Data resources on this research are secondary data. There are 15 stock company samples used on this research which were taken by using purposive sampling technique. The research methods used on this research are multiple regression and hypotheses test using t test and F test. Based on t test, current ratio, total asset turn over, debt to equity ratio, and earnings per share is not significance to stock return. Return on equity influences to stock return positively and significantly. Based on F test, simultaneously current ratio, total asset turn over, debt to equity ratio, return on equity, and earnings per share not influence to stock return.